Frequency doubler utilizing hetero gate dielectric tunnel field-effect transistor - Min, Ju Hong; Shin, Dongho; Kim, Hyunwoo; Kim, Jang Hyun (Physica Scripta, 2024)
With the rapid advancements in wireless communication and high-density integrated circuits, the demand for high-frequency sources has become paramount for transmitting vast amounts of information. Modern communication systems often utilize low-frequency sources at the transmitting end, converting them into high-frequency carriers through Intermediate Frequency (IF) for transmission to the receiving end. However, challenges arise in stabilizing high-frequency Voltage Controlled Oscillators (VCOs), leading to the necessity of Frequency Multipliers (FMs) in high-frequency circuits. While existing FMs face issues like harmonic distortion due to internal nonlinear devices, this paper proposes a single-device Frequency Doubler (FD) operation using Hetero-Gate Tunnel Field Effect Transistor (HG-TFET) with ambipolar characteristics. HG-TFET integrates high-κ (HK) materials and an HG structure in the gate dielectric, achieving independent control of tunneling distances and synchronous operation of source-to-channel and channel-to-drain tunneling currents (I SC and I CD) to facilitate FD operation. The paper presents the HG-TFET structure, process flow, and simulation models, followed by an exploration of its operating mechanism and characteristics. The FD circuit configuration, operational principles, and conditions for normal operation are detailed, emphasizing the importance of aligning I SC and I CD. The impact of adjusting HK lengths on I SC and I CD is analyzed, demonstrating the ability to independently control these currents through HG-TFET. Simulation results for FD operation under varying HK lengths (1-10 nm) validate the proposed approach. Additionally, the paper investigates the influence of dielectric constant (10-32) and gate dielectric thickness (2-5 nm) on FD performance, highlighting the potential for further optimization. In conclusion, this study establishes a foundation for normal FD operation through the symmetrical control of ambipolar and on currents using HG-TFET. The proposed structure and techniques open avenues for improving the efficiency and reliability of frequency-doubling applications in high-frequency circuits.
Keywords: Amount of information; Communications systems; Frequency multiplier; Frequency source; Hetero-gate dielectrics; High frequency circuits; High frequency HF; High-density integrated circuits; Lower frequencies; Wireless communications; frequency multiplier; hetero gate dielectric; tunnel field-effect transistor